PAVEMENT STRUCTURAL ASSESSMENT USING AUTOMATED TOOLS: A COMPARATIVE STUDY (Malaysian Journal of Civil Engineering, 2018)
Pavement distress evaluation was traditionally conducted through visual observation. Traditional practice requires a person to walk along the stretch of pavement in order to survey distresses, take photos, and measure defects occurred at the deteriorated surface. However, this approach is too subjective causes inconsistencies of information, less reliable and time-consuming. Due to these shortcomings, the practitioners in pavement maintenance sector seek for a reliable alternative tools and techniques to arrest incapability of traditional approach. This research aimed to investigate feasibility of automated tools for pavement structural assessment conducting a comparative study. Series of interviews with expert panels and comparison matrix have been conducted comparing Ground Penetrating Radar (GPR), Infrared Thermograph (IR), and Portable Seismic Pavement Analyzer (PSPA) by investigating across parameters; cost-time effectiveness, operating principle, depth of performance, method of application, and limitations of pavement evaluations. The research indicated the Ground Penetrating Radar (GPR) is highly advantageous over IR and PSPA for pavement structural assessment. The GPR, as a geophysical tool, has extensive capabilities to accommodate data in pavement assessment, geotechnical investigation and structural assessment. GPR can considerably perform at high speed and save time. It is also beneficial for long-term investment with deeper information. Notably, the interpretation of radar gram images of GPR tool needs sufficient time and skill.